Respuesta :
Answer:
-28
Step-by-step explanation:
x=-2 y=6
5x-3y
5(-2) -3(6)
= -10 -18
= -28
Answer:
-28
Step-by-step explanation:
Basically, this question is asking you to substitute the variables (x and y in this case) with numbers to solve the equation. Before we solve, let's replace those variables. So, if x = (-2), and y = 6, then:
5(-2) - 3(6).
We need to solve the equation from left to right. But we can't solve for the subtraction yet, because we need to solve for the multiplication first. So:
5 x (-2) = (-10) and 3 x 6 = 18.
Now we can subtract.
-10 - 18 = (-28).
Let me know if you have any more questions, I hope that this helps.